ANALISIS TAWAKAL DALAM AL-QURAN TERHADAP KESEHATAN MENTAL - Zubaidah, Ria; Abdul Ghofur (STAI Nurul Falah Airmolek, 2024)
This journal seeks to present the implications of tawakal for mental health. This research is a type of library research Library Research. The data analysis method that researchers use is the mau'dhui method. The research results show various phenomena regarding mental health that are still widely discussed. In daily life, of course there will be various problems that arise. As a result of the emergence of various problems faced, everyone can experience mental illness. When experiencing various kinds of anxiety, anxiety or worry about business results, the main key is trust. Being confident and believing that God's destiny is the best thing makes the mind calm. However, if you still have doubts about God's destiny, it will cause anxiety and worry which will have a negative impact on mental health. rom various previous studies conducted by researchers, the distinguishing factor in this journal's research is that it provides a more fundamental explanation of tawakkul (reliance on God) in relation to mental health. This analysis is examined through the lens of Quranic verses, specifically Q.S. Ali-Imran:122, Ali-Imran:173, Q.S. Hud:123, and At-Talaq:3 Keywords: Tawakal, Mental Health.